THE QUALITATIVE ASSESSMENT OF THE SPRING BARLEY GERMPLASM COLLECTION FROM ARDS TURDA - Ioana PORUMB; Florin RUSSU; Ana –Maria VĂLEAN; Cristina STANCĂ MOISE; Ioan ROTAR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The success of the amelioration experiments is closely connected to the coefficient of variation found at the genetic material level. The working collections of the amelioration programs don’t intend to conserve the whole existent diversity at the level of a species, just to a useful portion of it, adapted to the specific ecological zones to each amelioration program. In this idea, the assessment of diversity and genetic stability of the genotypes with different provenances is an important step into the breeding experiments. To obtain some information regarding the coefficient of variation and stability of some qualitative parameters of spring barley namely protein content, starch and TKW, they were analyzed 185 genotypes from the breed assortment of spring barley from ARDS Turda in two years of cultivation.